Da’wah and the 2019 Indonesian Presidential Election: A Closer Look to Da’wah Actors Activism and Methods - Fatmawati, Fatmawati; Minangsih, Kalsum; Noorhayati, Siti Mahmudah (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2020)
This article discusses intersection between dakwah and politics in contemporary Indonesia. It demonstrates the use of dakwah as political vehicle in electoral politics by looking at dakwah actors and their methods. Examining valuable sources, mainly online data, the article further concludes that the 2019 presidential election had led to the division within the dakwah actors. They are divided along the lines of presidential candidates and this division resonates clearly though their dakwah activism. From ideological perspectives, this article further finds out that dakwah actors and institutions with Islamist ideology inclines to vote for Prabowo Subijanto, whereas his rival as well as incumbent president Joko Widodo gains a significant support from the traditionalist Nahdlatul Ulama and the so-called “moderate Islam” had been central issue dividing the two.